Two new species of Emmallodera Blanchard, 1842 (Coleoptera: Tenebrionidae) from western Argentina - Silvestro, Violeta Ayelen (2012)
Two new species of the genus Emmallodera Blanchard (Tenebrioninae: Scotobiini) from western Argentina are described, Emmallodera rugosa sp. nov. from the Patagonian steppe and Emmallodera telteca sp. nov. from lowlands in the Mendoza province. Distributional data, habitat records, and photographs of habitus and pronota for these two new species are included, with comparisons to other known species of the genus.